Tren Penelitian Knowledge Sharing di Perpustakaan Perguruan Tinggi - Moethia Anggraeni; Tamara Adriani Salim (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to determine the development map regarding knowledge sharing in the university library. The research was conducted in December 2022 by searching through the Scopus database with the keywords knowledge sharing and university library. Data from search results were analyzed descriptively based on the year of publication, the country that published the progress of the research results, and the research subjects. To obtain a research development map, the data is exported into a Comma Separated Values (CSV) file format. The export data is then processed and analyzed using the VOSViewer application program to find out a bibliometric map of research developments regarding knowledge sharing in university libraries and of course provide research topics regarding Knowledge Sharing in University Libraries that can be researched in the future.